\(4\left(x-3\right)^2-2x\left(x-3\right)\)
Đặt nhân tử chung đa thức trên
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
=8x3y + z3y + 8x3z -2xz3 - y3(z +2x)= y(8x3+z3) +2xz(4x2-z2) - y3(2x+z) = y(2x+z)(4x2 - 2xz + z2) +2xz(2x+z)(2x-z) - y3(2x+z)
=(2x+z)(4x2y -2xyz + z2y + 4x2z -2xz2 - y3) = (2x+z)( 4x2y+ 4x2z - 2xyx- 2xz2 +z2y - y3) = (2x+z)[ 4x2(y+z) -2xz(y+z) + y(z+y)(z-y)]
= (2x+z)(y+z)( 4x2- 2xz +yz- y2) = (2x+z)(y+z)(4x2 - y2 -2xz + yz) = (2x+z)(y+z)[(2x-y)(2x+y) - z(2x-y)]
= (2x+y)(y+z)(2x-y)(2x+y-z)
a: \(5x\left(2x+3\right)+6x+9\)
\(=5x\left(2x+3\right)+\left(6x+9\right)\)
\(=5x\left(2x+3\right)+3\left(2x+3\right)\)
\(=\left(2x+3\right)\left(5x+3\right)\)
b: \(3x\left(x+4\right)+48\left(x+4\right)+5\left(x+4\right)\)
\(=\left(x+4\right)\left(3x+48+5\right)\)
=(x+4)(3x+53)
(x - 5)2 - 4(x - 3)2 + 2(2x - 1)(x - 5) + (2x - 1)2
= [(x - 5)2 + 2(2x - 1)(x - 5) + (2x - 1)2) - [2(x - 3)]2
= (x - 5 + 2x - 1)2 - (2x - 6)2
= (3x - 6)2 - (2x - 6)2
= (3x - 6 - 2x + 6)(3x - 6 + 2x - 6) = x(5x - 12)
( x - 5 )2 - 4( x - 3 )2 + 2( 2x - 1 )( x - 5 ) + ( 2x - 1 )2
= [ ( x - 5 )2 + 2( 2x - 1 )( x - 5 ) + ( 2x - 1 )2 ] - 22( x - 3 )2
= ( x - 5 + 2x - 1 )2 - ( 2x - 6 )2
= ( 3x - 6 )2 - ( 2x - 6 )2
= ( 3x - 6 - 2x + 6 )( 3x - 6 + 2x - 6 )
= x( 5x - 12 )
Đặt x^2+2x=t =>3t^2-2t-1=3t^2-3t+t-1=3t(t-1)+(t-1)=(t-1)(3t+1)
=>(x^2+2x-1)(3x^2+6x+1)
(x + 1)(x + 2)(x + 3)(x + 4) - 24
= x4 + 10x3 + 35x2 + 50x + 24 - 24
= x4 + 10x3 + 35x2 + 50x
( x + 1 ). ( x + 2 ) ( x + 3 ) ( x + 4 ) - 24
= ( x2 + 5x + 4 ) .( x2 + 5x + 6 ) - 24
Đặt t = x2 + 5x + 5
=> ( t - 1 ). ( t + 1 ) - 24
= t2 - 1 - 24
= t2 - 25
= ( t - 5 ). ( t + 5 )
= ( x2 + 5x + 5 - 5 ) . ( x2 + 5x + 5 + 5 )
= ( x2 + 5x ) . ( x2 + 5x + 10 )
= x. ( x + 5 ) . ( x2 + 5x + 10 )
Bài 1:
a. $2x^3+3x^2-2x=2x(x^2+3x-2)=2x[(x^2-2x)+(x-2)]$
$=2x[x(x-2)+(x-2)]=2x(x-2)(x+1)$
b.
$(x+1)(x+2)(x+3)(x+4)-24$
$=[(x+1)(x+4)][(x+2)(x+3)]-24$
$=(x^2+5x+4)(x^2+5x+6)-24$
$=a(a+2)-24$ (đặt $x^2+5x+4=a$)
$=a^2+2a-24=(a^2-4a)+(6a-24)$
$=a(a-4)+6(a-4)=(a-4)(a+6)=(x^2+5x)(x^2+5x+10)$
$=x(x+5)(x^2+5x+10)$
Bài 2:
a. ĐKXĐ: $x\neq 3; 4$
\(A=\frac{2x+1-(x+3)(x-3)+(2x-1)(x-4)}{(x-3)(x-4)}\\ =\frac{2x+1-(x^2-9)+(2x^2-9x+4)}{(x-3)(x-4)}\\ =\frac{x^2-7x+14}{(x-3)(x-4)}\)
b. $x^2+20=9x$
$\Leftrightarrow x^2-9x+20=0$
$\Leftrightarrow (x-4)(x-5)=0$
$\Rightarrow x=5$ (do $x\neq 4$)
Khi đó: $A=\frac{5^2-7.5+14}{(5-4)(5-3)}=2$
a, 4y(x-1)-(1-x)
=(x-1)(4y+1)
b,3x(z+2)+5(-x-2)
=3x(z+2)-5(x+2)
=(z+2)(3x-5)
4(x-3)2-2x(x-3)
=(x-3)(4x-12-2x)
=(x-3)(2x-12)
=(x-3).2(x-6)
=2(x-3)(x-6)
4(x-3)2-2x(x-3)
=2(x-3)(2x-6-x)
=2(x-3)(x-6)